Pengaruh Pemanfaatan Kelas Digital terhadap Prestasi Belajar Siswa di MA Unggulan KH. Abd. Wahab Hasbulloh Tambakberas Jombang - Yasaroh, Ririn Maskurin Ardila; Zulfah, Machnunah Ani; Hidayatulloh, Muhammad Kris Yuan (JoEMS (Journal of Education and Management Studies), 2022)
This study uses a type of field research. The research sample was 30 respondents. The research data that has been collected is then analyzed using statistical analysis techniques. Testing the research hypothesis using Product Moment correlation analysis. This research shows that: (1) The use of digital classes in MA Unggulan K.H.Abd.Wahab Hasbullloh Tambakberas Jombang is in the "Medium" category, which is in the 66-71 interval with an average value of 68.43. (2) Learning achievement in fiqh subjects at MA Superior KHAbd.Wahab Hasbulloh Tambakberas Jombang is included in the "High" category, which is in the 87-92 interval with an average value of 89. (3) student achievement in fiqh training for the 2019/2020 school year. This is based on the data that has been obtained by correlation rxy = 0.511> 0.361, with a significance level of "Medium" because it is in the position 0.40 - 0.599.